Handling and transportation of fish/shrimp seed-the weak link in the chain. - Mazuki Hashim (Malaysian Fisheries Society, 2024)
The production of seed represents one of the most important factors in the development of the aquaculture industry. The use of appropriate means of delivering fry in healthy and unstressed condition from hatchery to grow-out farm would thus represent a vital link in the seed production process. At the present, transport protocols employed by the industry have been developed on a trial and error basis. There is a need to develop transport protocols for various species of finfish, molluscs and shrimp based on the physiological requirements. Among other things, the protocols should address the need for proper conditioning regimes and transport bags and containers. Research should also orient towards long term effect of transport stress, particularly mechanical stress and the effect of transport chemicals, on the performance of the animal at the grow-out phase.